Consistency Between Treponema pallidum Particle Agglutination Assay and Architect Chemiluminescent Microparticle Immunoassay and Characterization of Inconsistent Samples. Issue 4 (19th May 2014) - Zhiyan, Li; Meiling, Wang; Ping, Liu; Jinhua, Dong; Zhenlin, Yan; Zhenru, Feng
<x xml:space="preserve">Abstract</x> Background Treponema pallidum particle agglutination assay (TPPA) has been shown to be highly sensitive and specific at detecting treponemal antibodies and is still used as a confirmatory method in many laboratories, in China. In clinical practice, we found that a significant number of TPPA‐negative sera were identified when TPPA was used as a confirmatory assay of Architect chemiluminescent microparticle immunoassay (CMIA) screening‐reactive sera. Aims To investigate the consistency between Architect CMIA and TPPA, and analyzed the characterization of TPPA‐negative sera following Screening by Architect CMIA. Methods According to the laboratory syphilis confirmatory testing protocol, a total of 4870 sera were initially tested by Architect CMIA and ELISA, and then the samples which shown positive results were tested by TPPA and rapid plasma reagin tests (RPR). Further analysis using Euroimmun dot‐immunoblot (dot‐IBT) assay was performed to the CMIA positive and TPPA negative samples. Results In our cohort, we found that the positive rate of CMIA was 3.1% (149/4870). One hundred and twelve of 112 (75.2%) CMIA‐positive sera were TPPA reactive, while 37 (24.8%) sera which were reactive in CMIA were nonreactive by TPPA. Dot‐IBT testing was performed on these 37 sera: 8 (21.6%) were dot‐IBT positive, 11 (29.7%) were indeterminate and 18 (48.6%) negative. Discussion In this study, we observed that 18 CMIA‐positive sera were false positives confirmed by dot‐IBT. But, given the relatively high levels of early syphilis, we consider a small increase in the number of confirmatory tests is worthwhile if we can increase the detection of primary syphilis by 20%. We also found that significant numbers (8/37) of CMIA‐positive and TPPA‐negative sera were shown by further dot‐IBT testing to be positive. The reason why certain sera are negative by TPPA but reactive by CMIA and other syphilis confirmatory assays is not clear, and these initial findings should be further explored. Conclusion The Architect CMIA is a highly sensitive screening assay for detecting syphilis but it is significantly less specific. Further analysis by TPPA is recommended to confirm the results. We would highlight the fact that in repeatedly screened populations discrepancies between treponemal CMIA and TPPA results are quite prevalent. This seems to be a function of very low levels of syphilis‐specific antibodies. Confirmation by immunoblot assay may be useful.